TECHNOLOGICAL ADAPTATION OF REFLECTIVE MATERIALS IN THE SYSTEM OF CONTEMPORARY FOOTWEAR DESIGN - Kuzina, Nataliia; Kernesh, V.Р.; Dubrovin, M.V. (SWorld-Ger Conference proceedings, 2025)
The article examines the technical aspects of implementing reflective elements in the design of modern footwear. Rational zones for their placement are analyzed, taking into account the structure of the product and visibility conditions in low-light envir